A Rare Occurrence of Bilateral Single-Rooted Mandibular First Molar - Urvashi Ujariya; Rajendra Bharatiya; Anjali Kothari; Viraj Shah; Mishri Parikh; Kruti Pandey; Dhara Mehta; Nishi Amin (Case Reports in Dentistry)
It is essential to have an in-depth knowledge of root and root canal anatomy to prevent any iatrogenic errors. Many studies and case reports are present in the literature related to the anatomy of mandibular first molars, but most of them are on an extra number of roots and root canals. There are few studies related to a lower number of roots and root canals, but the occurrence of bilateral mandibular first and second molars with the presence of root fusion resulting in a single root is very rare. This case report presents the nonsurgical endodontic management of the left and right mandibular first molars with the presence of a single root confirmed using a CBCT and treated by placing an apical MTA plug followed by backfill using thermoplasticised gutta percha.